DASH DIET IN THE PREVENTION AND TREATMENT OF ARTERIAL HYPERTENSION - Jelacik, Laura; Pozar, Hajnalka; Sumonja, Sanja (HEALTH CARE, 2022)
It is estimated that almost half of the adult population suffers from arterial hypertension in the Republic of Serbia. The development of arterial hypertension and its complications can be successfully controlled and prevented. The Dietary Approaches to Stop Hypertension, that is, the DASH diet is one of the most efficient dietary eating patterns in the control of hypertension. It leads to an average reduction in blood pressure by 4 to 15 mmHg, supports the optimization of body mass and lipids in the blood serum. The DASH diet promotes rational and balanced diet. In order to bring principles of the DASH diet closer to patients, it is necessary to adequately engage a nutritionist - dietician in working with high-risk patients. The paper presents practical recommendations for the implementation of the DASH diet and includes illustrations that serve to improve counseling work with patients in primary health care.
Keywords: hypertension, nutritionist, dietitian, education, DASH diet